Perfil de usuários de AASI com fissura labiopalatina - De Zambonato, Ticiana Cristina Freitas; Feniman, Mariza Ribeiro; Blasca, Wanderléia Quinhoneiro; Lauris, José Roberto Pereira; Maximino, Luciana Paula [UNESP] (My University, 2009)
Cleft palates cause alterations in palate and lip structures, and it may also cause hearing loss because of recurrent otitis media. The appropriate treatment is controversial. It may include the prescription of antibiotics and insertion of a ventilation tube, or even otorhinolaryngological and audiological assistance, and hearing rehabilitation, with the use of an individual sound amplifier aid (ISAA). Aim: To characterize the profile of individuals with cleft palate and hearing loss, users of ISAA are assisted by the center of otorhinolaryngology and speech therapy of a hospital specialized in craniofacial anomalies and hearing impairment. Retrospective Study. Material and Methods: Retrospective analysis of 131 charts of patients with corrected cleft palate and hearing loss, fitted with ISAA by the center abovementioned. Results: The sample (n=131) was characterized by a prevalence of females (53%), unilateral incisive transforaminal cleft (27%), presence of associated anomalies (51%), history of alterations of the middle ear (56%) and surgery intervention (56%). Conclusion: The general profile of the individuals with cleft palate and hearing loss, fitted with ISAA, was characterized by the predominance of cleft lip and palate, positive history of middle ear alterations, surgery intervention and bilateral sensorineural hearing loss. © Revista Brasileira de Otorrinolaringologia. All Rights reserved.
Profile of patients with cleft palate fitted with hearing AIDS
Keywords: Cleft palate; Conductive; Hearing loss; Mixed conductive-sensorineural; adolescent; adult; aged; child; cleft lip; cleft palate; female; hearing aid; hearing loss; human; male; middle aged; otitis media; preschool child; retrospective study; Adolescent; Adult; Aged; Child; Child, Preschool; Cleft Lip; Cleft Palate; Female; Hearing Aids; Hearing Loss; Humans; Male; Middle Aged; Otitis Media; Retrospective Studies; Young Adult